Greek μάρπτω and Tocharian A märk-* - Nikolaev, Alexander (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2022)
This paper examines the etymologically isolated Ancient Greek verb μάρπτω ‘to seize’ and argues that it is related to Tocharian A märk‑ ‘take away’ and possibly to Latin merx ‘commodity’ (with a semantic shift from ‘taking’ to ‘buying’). On the basis of these forms a new PIE root *merkw- is reconstructed.